Information and communication technologies applied to science education (2020)
The use of information and communication technologies [ICT] has proven to be accepted to increase students’ motivation, as it allows them to develop technological skills, creativity, and innovation. The objective of this research was to characterize the use of ICT in natural sciences as a factor associated with content learning in science, technology, and society [STS]. The sample consisted of 15 ninth-grade students and two teachers from the science area of a public educational institution in Colombia. The research was qualitative with a phenomenological approach. Non-participatory observation, semi-structured interviews,and qualitative content analysis were used. The change in student learning with the use of ICTs was observed in terms of the STS component. This use favoured motivation, attention, and participation during the development of the activities. Therefore, it is imperative to enhance science education from technological environments in order that students can provide solutions to problematic situations in their context.